EVALUASI PRODUK MODIS GROSS PRIMARY PRODUCTION PADA HUTAN RAWA GAMBUT TROPIS INDONESIA - Vetrita, Yenni; Hirano, Takashi (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2012)
Gross Primary Production (GPP) estimation method was developed as one approach for calculating the amount of carbon stored in vegetation. One of the GPP products which can be operationally downloaded free of charge from Terra/Aqua MODIS (NASA satellite) is MODIS GPP product (MOD17). The examination of this product needs to be performed in several ecosystem types due to its global properties. Recently, a new version of the product has been launched, however its examination on tropical forests particularly over Indonesia has not been implemented yet. In this study, new version of MODIS GPP (MOD17A2-51) was evaluated in tropical peat swamp forest, in Central Kalimantan Province using time series and statistical analysis of field data (GPP EC). The study results show that the time series of 8-daily MODIS GPP provide a similar pattern although it has low correlation. In general, MODIS GPP tend to be underestimate either on rainy or dry season. However, an overestimate result was found during the ENSO-caused long dry season in 2002. Nevertheless, the accumulated value of GPP with seasonal consideration (dry and rainy) shows good relationship (r=0.94, RMS= 17.47, and Efficiency score= 0.68). The 2nd dry season period (August-October) shows better distribution than other periods. This study concludes that the MODIS GPP product version 51 can be used for biomass seasonal monitoring of tropical peat swamp forests in Indonesia.